Dynamic Imaging Grade of Swallowing Toxicity (DIGEST): Scale development and validation. Issue 1 (26th August 2016) - Hutcheson, Katherine A.; Barrow, Martha P.; Barringer, Denise A.; Knott, Jodi K.; Lin, Heather Y.; Weber, Randal S.; Fuller, Clifton D.; Lai, Stephen Y.; Alvarez, Clare P.; Raut, Janhavi; Lazarus, Cathy L.; May, Annette; et al.
Abstract : BACKGROUND: The National Cancer Institute's Common Terminology Criteria for Adverse Events (CTCAE) is the universal framework for toxicity reporting in oncology trials. The objective of this study was to develop a CTCAE‐compatible modified barium swallow (MBS) grade for the purpose of grading pharyngeal dysphagia as a toxicity endpoint in cooperative‐group organ‐preservation trials for head and neck cancer (HNC). It was hypothesized that a 5‐point, CTCAE‐compatible MBS grade (Dynamic Imaging Grade of Swallowing Toxicity [DIGEST]) based on the interaction of pharyngeal residue and laryngeal penetration/aspiration ratings would be feasible and psychometrically sound. METHODS: A modified Delphi exercise was conducted for content validation, expert consensus, and operationalization of DIGEST criteria. Two blinded raters scored 100 MBSs conducted before or after surgical or nonsurgical organ preservation. Intrarater and interrater reliability was tested with weighted κ values. Criterion validity against oropharyngeal swallow efficiency (OPSE), the Modified Barium Swallow Impairment Profile (MBSImP™©), the MD Anderson Dysphagia Inventory (MDADI), and the Performance Status Scale for Head and Neck Cancer Patients (PSS‐HN) was assessed with a 1‐way analysis of variance and post hoc pairwise comparisons between DIGEST grades. RESULTS: Intrarater reliability was excellent (weighted κ = 0.82‐0.84) with substantial to almost perfect agreement between raters (weighted κ = 0.67‐0.81). DIGEST significantly discriminated levels of pharyngeal pathophysiology (MBSImP™©: r  = 0.77; P  < .0001), swallow efficiency (OPSE: r  = –0.56; P  < .0001), perceived dysphagia (MDADI: r  = –0.41; P  < .0001), and oral intake (PSS‐HN diet: r  = –0.49; P  < .0001). CONCLUSIONS: With the development of DIGEST, the MBS rating has been adapted to the CTCAE nomenclature of ordinal toxicity grading used in oncology trials. DIGEST offers a psychometrically sound measure for HNC clinical trials and investigations of toxicity profiles, dose responses, and predictive modeling. Cancer 2017;62–70. © 2016 American Cancer Society. Abstract : With the development of the Dynamic Imaging Grade of Swallowing Toxicity, the modified barium swallow rating has been adapted to the National Cancer Institute's Common Terminology Criteria for Adverse Events framework of ordinal toxicity grading used in oncology trials. The Dynamic Imaging Grade of Swallowing Toxicity offers a psychometrically sound measure of dysphagia for head and neck cancer clinical trials and for investigations of toxicity profiles, dose responses, and predictive modeling.